887 Suspected malignancy and unusual pathology in a severe case of Lemierre's syndrome. (12th October 2021) - Aruede, G; Ananth, S; Mustafa, S; Soukias, JM
Abstract: Lemierre's syndrome, although rare, is a potentially fatal condition, usually associated with the anaerobic bacterium, Fusobacterium necrophorum . This case describes a previously healthy 59-year-old female, who had a three-week history of pharyngitis and dysphagia. She presented to the emergency department with a left neck swelling and fever. A CT scan showed a 3 cm left level IV low-density suspected neck mass or necrotic node. There were multiple pulmonary nodules raising suspicion for metastases. Blood cultures were positive for Streptococcus constellatus and Dialister pneumosintes . The scan was further reviewed by a Head and Neck specialist radiologist and an Oral and Maxillofacial consultant, which highlighted a peritonsillar abscess and filling defect in the left internal jugular vein. A conclusive diagnosis of Lemierre's syndrome with septic pulmonary emboli was established. She improved clinically with IV antibiotics in conjunction with daily enoxaparin injections. We believe that this is the first reported case of Lemierre's syndrome associated with Dialister pneumosintes. A high index of suspicion is essential in cases of persistent pharyngitis and sepsis in an otherwise healthy individual, in order to promptly diagnose the condition and initiate treatment.